Qualidade socioambiental na bacia do rio Bacanga: implicações sobre o turismo e saúde das comunidades locais - COSTA, Josiane Moraes (2023)
Studies that use watersheds as an object of analysis allow the development of strategies under an integrative and environmental planning perspective.The Bacanga catchment area in Maranhão, on the São Luís island, corresponds to 12.33% of the territory, where approximately 64,000 households are located. The present work addresses the Bacanga watershed tourism potential, considering its landscape and the stakeholders; perceptions related to health and environment tourism. The research is divided into five sections. The first is the introduction. The second presents the theoretical framework based on a literature review proposing to discuss the connections regarding environmental quality, tourism, environmental perception, SWOT matrix, Brazilian environmental policy, and watersheds. From a conceptual and methodological perspective, the third section highlights the Tourist Potentials and Interfaces with the Environmental quality in the Bacanga basin, with six central tourist resources described, namely the Shipyard School Luiz Phelipe Andrès-Sítio Tamancão, the Bacanga lagoon, Sítio do Físico, Sítio Piranhenga, Ecological Trails -Trilha Eco Saber of the Federal Institute of Maranhão Maracanã (IFMA), and Maracanã Cultural Complex. The area has natural, cultural, historical, and archaeological resources such as parks, trails, lakes, and shell mounds. It is also a low tourism demand area due to the lack of publicity, infrastructure, and incentive from federal, state, and municipal public policies. Initially, a bibliographic review was carried out to characterize the singularities of the attractions, the existing environmental problems, and tourism impacts. The fourth section, “Landscape, Perceptions, and SWOT Analysis: a holistic approach to tourism management and environmental health of the Bacanga Basin”, uses the Institute of Historical and Artistic Heritage methodology, supported by a SWOT matrix analysis focused on health and environment tourism. Additionally, the chapter evaluates stakeholders perceptions using a survey and cartographic analysis. The results describe the singularities of the attractions, the existing environmental challenges, and how they impact tourism activity, bearing in mind the increasing importance and consolidation of local tourism. On the one hand, the research identified the region characteristics and potential for sustainable tourism development, as they are inserted in watersheds and can generate income and increase the quality of life of surrounding communities. On the other hand, challenges such as the greater participation of public agencies or private initiatives were also identified. Considering that the local potential identified may soon disappear due to the lack of municipal and state policies with interest in rescuing its value, the involvement of local stakeholders is suggested to develop effective strategies.